A mixed reception: perceptions of pregnant adolescents' experiences with health care workers in Cape Town, South Africa - Ronel Sewpaul; Rik Crutzen; Natisha Dukhi; Derrick Sekgala; Priscilla Reddy (BMC, 2021)
Plain language summary Antenatal care is the routine health care of pregnant women in order to diagnose pregnancy complications and to provide information about lifestyle, pregnancy and delivery. Maternal deaths among teenage mothers in South Africa is high and is largely due to conditions that can be prevented or managed by high quality antenatal care. Timely and routine antenatal care is therefore crucial for pregnant teenagers. The way in which pregnant teenagers are treated by health care workers at antenatal clinics influences their clinic attendance. This study reports on the experiences of pregnant teenagers with health care workers, when accessing antenatal care in Cape Town, South Africa. Nineteen pregnant girls aged 13-19 years were interviewed. Some positive experiences such as respectful and supportive treatment were reported. However, more negative experiences were reported, including victimization; discrimination against being pregnant at a young age; feeling disregarded and excluded; a lack of information about pregnancy, health and childbirth; being discouraged from attending the clinics; and mental health distress. In conclusion, many teenagers felt mistreated and discriminated against by the health care workers, which discouraged their clinic attendance. Maternal health care workers in South Africa need to receive support and regular training to provide youth friendly antenatal care to teenage girls.